Synthesis and Antidiabetic Evaluation of Some Novel Nitrogen containing Small Heterocyclic Derivatives (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
This article describes the synthesis, characterization and antidiabetic evaluation of some derivatives containing thiazolidinedione. The titled derivatives 4a-4y have been prepared by the condensation of chlorosulphonyl-benzylidine 2,4-thiazolidinedione with thiadiazole derivatives formed by the reaction of aromatic acid and thiosemicarbazide. The finalization of the reaction was affirmed by TLC and the structures of the derivatives were characterized and analyzed through FT-IR, 1H-NMR and 13C-NMR, Mass spectroscopy. Alloxan induced diabetes and oral glucose tolerance tests were done to evaluate for the anti-diabetic profile of the synthesized derivatives. Furthermore, docking of the compounds was done using V Life MDS software. The Dock score of the test compounds was in good correlation with the pharmacological activity results. The electron withdrawing substituents added on the core structure were more potent inhibitors than others.